Supramolecular nanoparticles that target phosphoinositide-3-kinase overcome insulin resistance and exert pronounced antitumor efficacy - Kulkarni, Ashish A.; Roy, Bhaskar; Rao, Poornima S.; Wyant, Gregory A.; Mahmoud, Ayaat; Ramachandran, Madhumitha; Sengupta, Poulomi; Goldman, Aaron; Kotamraju, Venkata Ramana; Basu, Sudipta; Mashelkar, Raghunath Anant; Ruoslahti, Erkki; et al. (Cancer Research, 2013)
The centrality of phosphoinositide-3-kinase (PI3K) in cancer etiology is well established, but clinical translation of PI3K inhibitors has been limited by feedback signaling, suboptimal intratumoral concentration, and an insulin resistance ``class effect.'' This study was designed to explore the use of supramolecular nanochemistry for targeting PI3K to enhance antitumor efficacy and potentially overcome these limitations. PI3K inhibitor structures were rationally modified using a cholesterol-based derivative, facilitating supramolecular nanoassembly with L-alpha-phosphatidylcholine and DSPE-PEG [1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polythylen e glycol)]. The supramolecular nanoparticles (SNP) that were assembled were physicochemically characterized and functionally evaluated in vitro. Antitumor efficacy was quantified in vivo using 4T1 breast cancer and K-Ras(LSL/+)/Pten(fl/fl) ovarian cancer models, with effects on glucose homeostasis evaluated using an insulin sensitivity test. The use of PI103 and PI828 as surrogate molecules to engineer the SNPs highlighted the need to keep design principles in perspective; specifically, potency of the active molecule and the linker chemistry were critical principles for efficacy, similar to antibody-drug conjugates. We found that the SNPs exerted a temporally sustained inhibition of phosphorylation of Akt, mTOR, S6K, and 4EBP in vivo. These effects were associated with increased antitumor efficacy and survival as compared with PI103 and PI828. Efficacy was further increased by decorating the nanoparticle surface with tumor-homing peptides. Notably, the use of SNPs abrogated the insulin resistance that has been associated widely with other PI3K inhibitors. This study provides a preclinical foundation for the use of supramolecular nanochemistry to overcome current challenges associated with PI3K inhibitors, offering a paradigm for extension to other molecularly targeted therapeutics being explored for cancer treatment. (C)2013 AACR.